Corporate governance as the driver of economic growth in Sub-Saharan African Countries - Martha Matashu; Wedzerai S. Musvoto (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2022)
Purpose: Corporate governance in essence is designed to lead to economic growth. Nevertheless, despite placing great emphasis on promoting corporate governance practices over the years, countries in Sub-Saharan Africa (SSA) have so far achieved insignificant or no economic growth. This, however, is inconsistent to the findings observed in developed countries. Design/methodology/approach: The study examined connections between corporate governance, macroeconomic fundamentals, the institutional environment and economic growth in Sub Saharan African countries. Panel Vector Autoregression (PVAR) models and impulse response functions were applied to analyse sets of panel data from 29 countries in Sub Saharan Africa for 7 years from 2008. Findings: The findings suggest that disaggregated variables of corporate governance, macroeconomic fundamentals and the institutional environment have a positive but insignificant relationship with economic growth. It was also found that aggregated composite; corporate governance, macroeconomic fundamentals and the institutional environment have a statistically strong significant relationship with economic growth. The results of the impulse response functions predict that, there will be a 0.01 per cent growth in the economies of Sub-Saharan African countries if there is a continued interaction between aggregated variables under the present conditions observed during the period of the investigation. The PVAR results showed that the future outcome of economic growth can be predicted from the past behaviour of aggregated composite corporate governance. The impulse response and variance deposition. The findings lead to the conclusion that aggregated corporate governance within both a given year and that of previous periods are major determinants of economic growth. Research limitations/implications: The implications of the findings for countries within Sub Saharan Africa is that promoting corporate governance only might be insufficient to stimulate growth of economies, rather it must be enhanced concurrently with macroeconomic fundamentals and the institutional environment. If past behaviour is a contributing factor of the future performance of corporate governance then, a reflection on the past governance behaviour can help to develop effective corporate governance practices that affect the present and future economic growth. Originality/value: This study contributes to literature by testing application the theoretical relevance of corporate governance theories to the context of Sub-Saharan African countries economies. The findings suggest that sound corporate governance on its owned is insufficient to stimulate and sustain to economic growth within countries under investigation. As, adduced by evidence corporate governance affect economic growth is context dependent. More attention can be paid to examining the link corporate governance linkages to economic growth in different contexts in future studies.
Keywords: G32; L25; L30; O34; 330; Corporate governance; Legal system; Good governance; Financial development; Macroeconomic fundamentals; economic growth; panel vector autoregression; impulse response functions